PENGEMBANGAN MODEL BIMBINGAN TEKNIS BERKELANJUTAN DALAM MENINGKATKAN KOMPETENSI TUTOR PAKET C - Anan Sutisna (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2015)
This study aims at finding a model of Sustainable Technical Assistance that can improve the Package C tutors’competence. The alternative model selected to achieve the research objective was by developing a model based on Sustainable Technical Assistance and focusing on the tutors’ technical ability to perform their instructional tasks. The development of this model was based on the assumption that the previous model was conducted partially, much oriented on cognitive aspect, and conducted in conventional ways, and the content did not fit to the participants’ needs. The Sustainable Technical Assistance model was developed applying research and development approach. The results showed that the model needs to be tried out to improve the pedagogical competence of Package C tutors at the national standard.